THE REALIZATION OF INTERPERSONAL MEANING ON MALE AND FEMALE STUDENTS’ PERSONAL LETTER - Dewi Nasita; Bambang Ruby Sugiarto; Luthfiyatun Thoyyibah (Universitas Galuh, 2020)
Interpersonal meaning is important since it reveals someone’s adjustment into another participant, it is created and maintained the social relations (Gerrot and Wignell, 1994). The present study proposed to elaborate the similarity or the difference between the realization of interpersonal meaning on male and female students’ letters, especially personal letters and to investigate which one between male and female students is more emotionally expressive in writing a personal letter. The present study implemented discourse analysis in the qualitative descriptive design. Three couples of male and female students in the eleventh grade at one of Senior High School in Ciamis, Indonesia were engaged in this study. Six personal letters then analyzed by means of Systemic Functional Linguistics. It was found that both male and female students created a sense of politeness in a different way. Thus, the majority of declarative clauses evinced that both male and female students comprehended well the purpose of the letter-writing which is to give information. In terms of modality, female students presented lower modalization which is suggested that they preferred to present the information as what it has. Moreover, female students found dominated all the characteristics of emotional markers. It significantly proofed that female students are more emotionally expressive rather than male students.Keywords: Interpersonal Meaning, Gender Differences, Emotional Expression, Personal Letter